KEMAMPUAN MENULIS LAMBANG BILANGAN数字(shù zì) BAHASA MANDARIN SISWA SMA CELEBES GLOBAL SCHOOL MAKASSAR - Maemunah Maemuah; Misnawaty Usman; Hasmawati Hasmawati (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2022)
Maemunah, 2021. Ability to Write Number Symbols (shù zì) in Chinese for High School Students Celebes Global School Makassar. Thesis. Mandarin Language Education Study Program, Department of Foreign Languages, Faculty of Languages and Literature. Makassar State University (supervised by Misnawaty Usman and Hasmawati).This research is a descriptive quantitative research to describe the students’ ability to write Mandarin numbers at the 10th grade of SMA Celebes Global School Makassar which collected 14 students of class X of SMA Celebes Global School. The data of this study was gathered throght tests and documentation. The analysis result shows that the students’ ability to write the Mandarin numeric number is 81% or in good category. Keywords: Ability, Mandarin, Writing Chinese Characters, Number Symbols